2021
DOI: 10.1080/14992027.2021.1948120
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the benefit of hearing aids with motion-based beamformer adaptation in a real-world setup

Abstract: Objective: Conventional directional hearing aid microphone technology may obstruct listening intentions when the talker and listener walk side by side. The purpose of the current study was to evaluate hearing aids that use a motion sensor to address listening needs during walking. Design: Each participant completed two walks in randomised order, one walk with each of two hearing aid programs: (1) conventional beamformer adaptation that activated an adaptive, multiband beamformer in loud environments and (2) mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…It operates independently on the CI and HA. The algorithm is an adaptive multiband beamformer (Voss et al, 2021) and attempts to maximize the attenuation of sounds originating from the back hemisphere by estimating the region with the lowest signal-to-noise ratio (SNR) in the auditory scene. The region of maximal attenuation (the null direction) is steered toward the noise-dominated region, potentially further increasing the SNR by noise suppression (Buechner et al, 2014;Hehrmann et al, 2012).…”
Section: Contralateral Hearing Aid Fitting For Home Usementioning
confidence: 99%
“…It operates independently on the CI and HA. The algorithm is an adaptive multiband beamformer (Voss et al, 2021) and attempts to maximize the attenuation of sounds originating from the back hemisphere by estimating the region with the lowest signal-to-noise ratio (SNR) in the auditory scene. The region of maximal attenuation (the null direction) is steered toward the noise-dominated region, potentially further increasing the SNR by noise suppression (Buechner et al, 2014;Hehrmann et al, 2012).…”
Section: Contralateral Hearing Aid Fitting For Home Usementioning
confidence: 99%
“…Those systems can be used to steer audio processing algorithms aiming at enhancing speech intelligibility and/or spatial awareness [4,5]. Voss et al [6] showed significant improvement in speech understanding, sound localization as well as preference in hearing-impaired listeners with such steering approaches. Being able to track the head motions of a user is of high interest since this would allow controlling the beam of a directional microphone system for example.…”
Section: Introductionmentioning
confidence: 99%